Laminate and manufacturing method thereof

The laminate structure, featuring a thermoplastic film with a porous structure bonded to a fiber-reinforced thermosetting resin layer, addresses the limitations of existing bonding methods by enhancing bonding strength and versatility through resin impregnation.

JP2025062211APending Publication Date: 2025-04-14TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023171130
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing methods for bonding fiber-reinforced thermosetting resin layers with thermoplastic resin layers rely solely on the affinity between resin species, limiting the types of resins that can be used and resulting in inadequate bonding strength.

Method used

A laminate structure is developed where a thermoplastic film with a porous structure is laminated onto a fiber-reinforced thermosetting resin layer, with the thermoplastic film's pore diameter ranging from 0.01 μm to 30 μm, allowing the thermosetting resin to impregnate the pores and enhance bonding.

Benefits of technology

This approach enables a strong and durable bond between the thermosetting resin and thermoplastic layers without relying on resin affinity, allowing for a wider range of resin combinations and improved mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062211000001
    Figure 2025062211000001
Patent Text Reader

Abstract

To provide a laminate capable of firmly bonding a fiber-reinforced thermosetting resin layer and a thermoplastic resin layer, regardless of an affinity between resin types.SOLUTION: A laminate in which a thermoplastic film (C) having a porous structure is laminated on a surface of a layer consisting of reinforcing fibers (A) and a thermosetting resin (B), in which a diameter of pores of the thermoplastic film (C) is 0.01 μm or more and 30 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate of a fiber-reinforced thermosetting resin layer and a thermoplastic film, and a method for producing the same. [Background technology]

[0002] Fiber-reinforced composite materials, which are made by combining reinforcing fibers with thermosetting resins, are excellent in light weight, mechanical properties, and dimensional stability, and are therefore used in a wide range of fields, such as aircraft and other transportation equipment, electrical and electronic equipment, sporting goods, and building materials. Such fiber-reinforced composite materials may be used with a thermoplastic resin member bonded to their surface. For this reason, attempts have been made to provide a thermoplastic resin layer on the surface of the fiber-reinforced composite material and to weld the thermoplastic resin member through the thermoplastic resin layer.

[0003] As an example, Patent Document 1 and Non-Patent Document 1 describe a method in which a film of a thermoplastic resin that has a relatively high affinity with a thermosetting resin is placed on an uncured prepreg, which is a precursor of a fiber-reinforced composite material, and a mixed layer in which the thermosetting resin of the prepreg and the thermoplastic resin of the film are mixed is formed at the interface, thereby bonding the prepreg and the film to form a thermoplastic resin layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2022 / 181423 [Non-patent literature]

[0005] [Non-Patent Document 1] Investigation on Energy Director-less Ultrasonic Welding of Polyetherimide (PEI)- to Epoxy-based Composites. (Composites Part B: Engineering Volume 173,15 September 2019) Summary of the Invention [Problem to be solved by the invention]

[0006] However, the methods shown in Patent Document 1 and Non-Patent Document 1 bond the prepreg and the film only based on the affinity of the resin species between the thermosetting resin and the thermoplastic resin, so there are limitations on the resins that can be applied. An object of the present invention is to provide a laminate that can firmly bond a fiber-reinforced thermosetting resin layer and a thermoplastic resin layer without relying on the affinity of the resin species. [Means for solving the problem]

[0007] The present invention relates to a laminate in which a thermoplastic film (C) having a porous structure is laminated on the surface of a layer consisting of reinforcing fibers (A) and a thermosetting resin (B), and the diameter of the pores of the thermoplastic film (C) is 0.01 μm or more and 30 μm or less. Effect of the Invention

[0008] The configuration of the laminate of the present invention makes it possible to firmly bond the fiber-reinforced thermosetting resin layer and the thermoplastic resin layer, regardless of the types of thermosetting resin and thermoplastic resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The laminate of the present invention and the method for producing the same will be described in detail below.

[0010] The laminate of the present invention is a laminate obtained by laminating a layer consisting of reinforcing fibers (A) and a thermosetting resin (B) (hereinafter referred to as a "fiber-reinforced thermosetting resin layer") and a thermoplastic film (C) having a porous structure, in which the diameter of the pores of the thermoplastic film (C) is 0.01 μm or more and 30 μm or less.

[0011] The laminate of the present invention includes both cases where the thermosetting resin (B) is uncured (non-gelled) and cured (gelled). The gelation of the thermosetting resin (B) can be determined based on the magnitude relationship between the storage modulus and the loss modulus. Specifically, when the storage modulus measured at 25°C is equal to or less than the loss modulus, it is determined to be uncured since it has not gelled, and when the storage modulus is greater than the loss modulus, it is determined to be cured since it has gelled. The storage modulus and loss modulus of the thermosetting resin (B) are measured using a dynamic viscoelasticity analyzer based on JIS K7244-10 (2005).

[0012] In the present invention, it is preferable that the thermosetting resin (B) is impregnated into the pores constituting the porous structure of the thermoplastic film (C), and the impregnation distance of the thermosetting resin (B) into the thermoplastic resin layer is preferably 5 μm or more. The impregnation distance is obtained by observing a cross section of the laminate cut so that the surface layer is in the 0° direction with a microscope and measuring the distance from the interface between the fiber-reinforced thermosetting resin layer and the thermoplastic resin layer to the position where the thermosetting resin (B) penetrates. Here, the impregnation distance is obtained by taking a photograph at a magnification of 1000 times in the microscope observation, measuring the position where the thermosetting resin (B) penetrates deepest from the interface between the fiber-reinforced thermosetting resin layer and the thermoplastic resin layer in the cross section photograph, and performing this operation at 20 points, and the average value is the impregnation distance. By impregnating the pores of the thermoplastic film (C) with the thermosetting resin (B), both the thermoplastic film (C) and the fiber-reinforced thermosetting resin layer are firmly bonded to each other.

[0013] The porous structure of the thermoplastic film (C) is preferably a structure in which pores are continuously distributed. With such a structure, the thermosetting resin (B) is impregnated into the continuous pores, and the impregnated thermosetting resin (B) and the thermoplastic film (C) form a complex interface over a wide area, and both the thermoplastic film (C) and the fiber-reinforced thermosetting resin are firmly bonded to each other.

[0014] The diameter of the pores in the thermoplastic film (C) is preferably 30 μm or less, and more preferably 10 μm or less. There is no particular lower limit to the diameter of the pores, but it is generally 0.01 μm or more. By setting the diameter in such a range, the thermosetting resin (B) penetrates finely when impregnated, and both the thermoplastic film (C) and the fiber-reinforced thermosetting resin layers are firmly bonded. Here, the diameter of the pores is the pore diameter corresponding to a pore volume ratio of 50% on a distribution curve obtained by mercury intrusion porosimetry.

[0015] <Reinforced fiber (A)> The reinforcing fibers (A) are, for example, glass fibers made of E glass, C glass, S glass, D glass, etc., polyacrylonitrile-based, rayon-based, lignin-based, pitch-based carbon fibers, metal fibers made of stainless steel, iron, gold, silver, aluminum, alloys thereof, aromatic polyamide fibers, polyaramid fibers, alumina fibers, silicon carbide fibers, boron fibers, and ceramic fibers, for the purpose of expressing mechanical properties such as strength and elastic modulus of the laminate. These are used alone or in combination of two or more. As the reinforcing fibers (A), metal fibers, glass fibers, and carbon fibers are preferred from the viewpoint of high strength and high elastic modulus, and among them, carbon fibers, which have a low specific gravity and excellent specific strength and specific rigidity, are preferably used from the viewpoint of light weight. In particular, polyacrylonitrile-based carbon fibers are preferably used from the viewpoint of realizing low production costs.

[0016] The reinforcing fiber (A) may be surface-treated. Examples of surface treatment include metal deposition, coupling agent treatment, sizing agent treatment, and additive attachment treatment. The sizing agent is not particularly limited, but is preferably a compound having at least one functional group selected from the group consisting of carboxyl groups, amino groups, hydroxyl groups, and epoxy groups in one molecule, in which there are three or more functional groups. Two or more types of functional groups may be mixed in one molecule, and two or more types of compounds having one type of functional group in one molecule in which there are three or more functional groups may be used in combination.

[0017] The form of the reinforcing fiber (A) may be a continuous fiber form, such as a strand consisting of a large number of filaments, a cloth such as a plain weave, satin weave, or twill weave composed of the strand, a strand in which a large number of filaments are arranged in one direction (unidirectional strand), or a unidirectional cloth composed of the unidirectional strand. The term "continuous fiber" refers to a linear fiber having a length of 10 mm or more, and is preferably a fiber having a length from one end to the opposite end in a laminate. From the viewpoint of exhibiting high mechanical properties, a reinforcing fiber in the form of a continuous fiber is preferably used. The form of the reinforcing fiber (A) may also be a fiber dispersion form in which strands and / or single fibers of the reinforcing fiber are dispersed in a planar shape, such as a chopped strand mat, a papermaking mat, a carding mat, or an airlaid mat, and from the viewpoint of shape imparting, a fiber dispersion form is preferable.

[0018] <Thermosetting resin (B)> Examples of the thermosetting resin (B) include unsaturated polyester, vinyl ester, epoxy, phenol (resole type), urea-melamine, polyimide, copolymers, modified products, and blends of at least two of these resins. From the viewpoint of improving impact resistance, an elastomer or rubber component may be added to the thermosetting resin (B).

[0019] The thermosetting resin (B) particularly suitable for the present invention is an epoxy resin, which is generally used in combination with a curing agent or a curing catalyst. In particular, epoxy resins having precursors of amines, phenols, and compounds having carbon-carbon double bonds are preferred. Specifically, epoxy resins having precursors of amines include various isomers of tetraglycidyldiaminodiphenylmethane, triglycidyl-p-aminophenol, triglycidyl-m-aminophenol, and triglycidylaminocresol, epoxy resins having precursors of phenols include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, and cresol novolac type epoxy resin, and epoxy resins having precursors of compounds having carbon-carbon double bonds include, but are not limited to, alicyclic epoxy resins. Brominated epoxy resins obtained by brominating these epoxy resins may also be used. Epoxy resins having precursors of aromatic amines, such as tetraglycidyldiaminodiphenylmethane, are most suitable for the present invention because they have good heat resistance and good adhesion to the reinforcing fibers (A).

[0020] Epoxy resins are preferably used in combination with epoxy curing agents. Any compound having an active group capable of reacting with an epoxy group can be used as the epoxy curing agent. Compounds having an amino group, an acid anhydride group, or an azide group are preferable. Specifically, dicyandiamide, various isomers of diaminodiphenyl sulfone, and aminobenzoic acid esters are suitable. More specifically, dicyandiamide is preferably used because it provides excellent preservation properties for prepregs. Also, various isomers of diaminodiphenyl sulfone are most suitable for the present invention because they give cured products with good heat resistance.

[0021] <Thermoplastic film (C)> The thermoplastic resin of the thermoplastic film (C) having a porous structure is not particularly limited, and examples thereof include polyester-based resins such as polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polytrimethylene terephthalate (PTT) resin, polyethylene naphthalate (PENp) resin, and liquid crystal polyester; polyolefin resins such as polyethylene (PE) resin, polypropylene (PP) resin, and polybutylene resin; styrene-based resins; and urethane resins; polyoxymethylene (POM) resin, polyamide (PA) resin, polycarbonate (PC) resin, polymethyl methacrylate (PMMA) resin, polyvinyl chloride (PVC) resin, and the like. ) resin, polyarylene sulfide (PAS) resin such as polyphenylene sulfide (PPS) resin, polyethersulfone (PES) resin, polyamideimide (PAI) resin, polyetherimide (PEI) resin, polysulfone (PSU) resin, modified PSU resin, polyketone (PK) resin, polyetherketone (PEK) resin, polyetheretherketone (PEEK) resin, polyetherketoneketone (PEKK) resin, polyarylate (PAR) resin, polyethernitrile (PEN) resin, thermoplastic polyimide (PI) resin, polyphenylene ether (PPE) resin, modified PPE resin, and polyamide (PA) resin are exemplified. In addition, these thermoplastic resins may be copolymers or modified bodies of the above-mentioned thermoplastic resins, and / or resins blended with two or more kinds of them, and may further contain other fillers or additives as appropriate within the scope of the present invention depending on the application. For example, a flame retardant can be added to enhance the flame retardancy of the thermoplastic resin.

[0022] The method for obtaining the thermoplastic film (C) of the present invention is not particularly limited, but includes a dry method in which a resin is melted, extruded into a sheet, and then stretched to make it porous, and a wet method in which a phase-separating component is contained in the film precursor and then extracted with a solvent or the like to form holes. In the dry method, a method in which inorganic particles are added and stretched to form holes around the particles as nuclei, and a method in which the crystal interface is peeled off by stretching to form holes are preferably used. In particular, in the method including stretching, fibrils are generated around the holes, so that complex holes can be formed, and when the thermosetting resin (B) is impregnated, a complex interface is formed, and both the thermoplastic film (C) and the fiber-reinforced thermosetting resin layers are firmly bonded.

[0023] The thickness of the thermoplastic film (C) is preferably thinner than the thickness of the layer consisting of the reinforcing fiber (A) and the thermosetting resin (B) since the film is prone to warping after molding if it is too thick. The specific thickness of the thermoplastic film (C) is preferably 500 μm or less, more preferably 300 μm or less. The lower limit of the thickness is not particularly limited, but is generally 1 μm or more.

[0024] It is preferable that the thermoplastic film (C) forming the thermoplastic resin layer has openings of a porous structure on the surface in contact with the thermosetting fiber reinforced resin layer. In this way, a part of the thermosetting resin (B) penetrates into the pores of the thermoplastic film (C), and the thermoplastic film (C) and the layer consisting of the reinforcing fiber (A) and the thermosetting resin (B) are mechanically fastened together, so that the two layers are firmly bonded together.

[0025] In order to enhance the adhesion at the bonding surface with the thermosetting resin (B), an adhesive component may be applied to the surface of the thermoplastic film (C) to bond it to the fiber-reinforced thermosetting resin layer. From the viewpoint of enhancing the bonding strength, it is preferable that the adhesive component is attached to 70% or more of the surface of the thermoplastic film (C), more preferably 90% or more, and evenly attached to the entire surface. There is no particular limitation on the adhesive component, but from the viewpoint of enhancing adhesion, a compound containing one or more functional groups having high reactivity or interaction in the molecule is preferable. Examples of the functional group include a carboxyl group, a glycidyl group, an amino group, an isocyanate group, an acid anhydride group, a hydroxyl group, an amide group, and an ester group, among which, a carboxyl group, a glycidyl group, an amino group, an isocyanate group, and an acid anhydride group are highly reactive functional groups and are preferable. Furthermore, from the viewpoint of enhancing adhesion, a compound having two or more of the functional groups is preferable. From the viewpoint of affinity with the thermoplastic film (C), the compound is preferably an organic compound, a polymer compound, or an organosilicon compound. Preferable examples of organic compounds include trimellitimide compounds such as N,N'-ethylene bistrimellitimide and N,N'-hexamethylene bistrimellitimide, and polyfunctional aromatic epoxies include bisphenol A, resorcinol, hydroquinone, bisphenol S, and bisphenol-glycidyl ether epoxy compounds such as 4,4'-dihydroxybiphenyl. Preferable examples of polymer compounds include acid-modified polyolefins such as ethylene-ethyl acrylate copolymers and maleic anhydride-modified polypropylene, and epoxy-modified polyolefins such as ethylene-glycidyl methacrylate copolymers. Preferable examples of organosilicon compounds include glycidyl-modified organosilane compounds such as γ-glycidoxypropyltrimethoxysilane, isocyanate-modified organosilane compounds such as 3-isocyanatepropyltriethoxysilane, and amino-modified organosilane compounds such as 3-aminopropyltrimethoxysilane and N-2-(aminoethyl)-3-aminopropyltrimethoxysilane.

[0026] There are no particular limitations on the method for applying such an adhesive component to the surface of the thermoplastic film (C). In the case of a solid material, there are methods for adhering a crushed powder to the thermoplastic film (C) and methods for melting the compound and applying it. However, as a uniform and simple application method, a method for immersing the thermoplastic film (C) in a liquid of a predetermined concentration in which the compound is dissolved or dispersed in an organic solvent or water and then drying it, or a method for spraying the compound with a spray and then drying it, is preferred.

[0027] <Method of manufacturing laminate> As described above, the laminate of the present invention includes a laminate in which the thermosetting resin (B) is uncured and a laminate in which the thermosetting resin (B) is cured. There is no particular limitation on the method for producing the laminate of the present invention, but a laminate in which the thermosetting resin (B) is impregnated into the pores of the thermoplastic film (C) can be obtained by producing it by the following method.

[0028] In the case of a laminate in which the thermosetting resin (B) is uncured, the laminate can be produced by a method in which a preform in which a thermoplastic film (C) having a porous structure is laminated on the surface of a prepreg made of reinforcing fibers (A) and uncured thermosetting resin (B) is pressurized at room temperature or at a temperature at which the thermosetting resin (B) does not cure, thereby impregnating the porous structure portion of the thermoplastic resin film (C) with the thermosetting resin (B).

[0029] In the case of a laminate in which the thermosetting resin (B) is cured, a preform in which a thermoplastic film (C) having a porous structure is laminated on the surface of a prepreg made of reinforcing fiber (A) and thermosetting resin (B) is heated to a temperature at which the thermosetting resin (B) is cured and pressurized, thereby impregnating the thermosetting resin (B) and curing the thermosetting resin (B). This method can be carried out in one step, and is therefore preferable from the viewpoint of processability.

[0030] Alternatively, the laminate in which the thermosetting resin (B) is cured can also be produced by a method in which a laminate in which the thermosetting resin (B) is uncured as described above is produced, and then the thermosetting resin (B) is cured. This method is preferable from the viewpoint of sufficient impregnation of the thermosetting resin (B) since the thermosetting resin (B) can be impregnated into the thermoplastic resin film in a low viscosity state. It is preferable that the thermoplastic film (C) having a porous structure does not soften at the temperature at which the thermosetting resin (B) is cured. Here, the "temperature at which the thermosetting resin (B) is cured" refers to the temperature of the first stage when the thermosetting resin (B) is cured in multiple stages. In addition, whether the thermoplastic film (C) softens or not is judged by the deflection temperature under load measured based on the B method of JIS K 7191. Specifically, the relationship between the deflection temperature under load Td (°C) of the thermoplastic film (C) and the curing temperature Tp (°C) when the thermosetting resin (B) is molded is preferably Td>Tp, more preferably Td-Tp≧10 (°C), more preferably Td-Tp≧30 (°C), and even more preferably Td-T≧50 (°C). By designing in this way, when the viscosity of the thermosetting resin (B) is reduced by heating, the thermoplastic film (C) having a porous structure is impregnated with the thermosetting resin (B) in the pores while maintaining a continuous porous structure, and when the thermosetting resin (B) penetrates into the pores, the pores of the thermoplastic film can maintain a continuous structure in the thickness direction and in-plane direction, and the thermoplastic film (C) and the fiber-reinforced thermosetting resin layer are firmly bonded. EXAMPLES

[0031] The present invention will be described in more detail below with reference to examples. First, the evaluation methods used in the present invention will be described below.

[0032] (Evaluation method 1) Deflection temperature under load Td of thermoplastic resin film (C) The deflection temperature under load was measured for a sample injection molded from the resin used for thermoplastic film (C) in accordance with "Plastics - Determination of deflection temperature under load" as stipulated in JIS-K7191 (2015) Method B. The above procedure was repeated three times, and the average of the temperatures obtained was calculated to determine the deflection temperature under load of thermoplastic film (C).

[0033] (Evaluation method 2) Diameter of holes in thermoplastic resin film The pore size distribution curve of the thermoplastic film (C) was obtained using an Autopore IV9510 manufactured by Micromeritics as a mercury intrusion porosimeter. The pore size corresponding to a pore volume ratio of 50% on the distribution curve was taken as the diameter of the pores in the thermoplastic film (C).

[0034] (Evaluation method 3) Observation of the porous structure of the film After cutting the film with a cutter, the cross section was photographed at 30 locations at 1000x magnification using a digital microscope (Keyence, VHX-5000). The percentage of holes was calculated from the overall ratio using formula 1 by mapping the color difference between the holes and other areas. Percentage of holes [%] = (area of ​​holes in observed cross section) / (total area of ​​observed cross section) × 100 (Equation 1) (Evaluation method 4) Cross-sectional observation of molded product The cross section of the laminate was polished and photographed at 1000x magnification using a laser microscope (Keyence Corporation, VHX-5000). In the cross section photograph, the position where the thermosetting resin (B) penetrated deepest from the interface between the fiber-reinforced thermosetting resin layer and the thermoplastic film (C) was measured. This operation was performed at 20 points, and the average value was taken as the impregnation distance of the thermosetting resin (B).

[0035] <Materials used in the Examples and Comparative Examples> <Reinforced fiber (A)> A polymer mainly composed of polyacrylonitrile was spun and sintered to obtain continuous carbon fibers with a total of 12,000 filaments. The continuous carbon fibers were then electrolytically surface-treated and dried in heated air at 120°C to obtain carbon fibers. The properties of the carbon fibers were as follows:

[0036] Density: 1.80g / cm 3 Single fiber diameter: 7μm Tensile strength: 4.9GPa Tensile modulus: 230GPa <Thermosetting resin (B)> "Epotohto (registered trademark)" YD-128 (bisphenol A type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.: epoxy equivalent 190g / eq) "Epotohto (registered trademark)" YD-128G (bisphenol A type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.: epoxy equivalent 190g / eq) "jER (registered trademark)" 1001 (bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation: epoxy equivalent 475g / eq) "jER (registered trademark)" 1009 (bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation: epoxy equivalent 2750g / eq) Hardener DICY7 (Dicyandiamide, manufactured by Mitsubishi Chemical Corporation, molecular weight 84g / mol) curing catalyst DCMU99 (3-(3,4-dichlorophenyl)-1,1-dimethylurea, (Manufactured by Hodogaya Chemical Co., Ltd.) Additives "Vinylec" (registered trademark) K (polyvinyl formal, manufactured by JNC Corporation).

[0037] <Thermosetting resin composition> In a kneading device, 40 parts by mass of "Epotohto (registered trademark)" YD-128, 20 parts by mass of "Epotohto (registered trademark)" YD-128G, 20 parts by mass of "jER (registered trademark)" 1001, 20 parts by mass of "jER (registered trademark)" 1009, and 5 parts by mass of additive "Vinylec (registered trademark) K" were added as epoxy resins, and the temperature was raised to 160 ° C., and kneaded at 160 ° C. for 30 minutes. After that, while continuing kneading, the temperature was lowered to 55 to 65 ° C., and the curing agent and curing catalyst DICY7 and DCMU99 were added and stirred for 30 minutes to obtain a thermosetting resin composition.

[0038] <Thermosetting prepreg> A large number of reinforcing fiber groups were formed by arranging carbon fibers in one direction, and the carbon fibers were impregnated with a thermosetting resin composition so that the carbon fiber content was 67% by mass fraction (Wf) to obtain a prepreg.

[0039] <Thermoplastic film having a porous structure (C)> ·Porous film (C-1) PPS resin ("TORELINA" M2888, manufactured by Toray Industries, Inc.) was mixed with 60% by weight of calcium carbonate powder having an average particle size of 3 μm, melt-kneaded in a twin-screw extruder, extruded into a strand shape, cut with a cutter, and pelletized to obtain a PPS resin composition 1. The obtained pellets were vacuum-dried, fed to an extruder, melt-extruded while heated, and the extruded molten resin was rapidly cooled and solidified to obtain an unstretched PPS sheet. The unstretched PPS sheet was made to contact and run between multiple heating rolls, stretched in the film take-up direction between cooling rolls with different peripheral speeds installed next to the heating rolls, and then stretched in the direction perpendicular to the film take-up direction using a tenter, followed by heat treatment, followed by relaxation treatment, and cooled to room temperature to obtain a porous film (C-1) with a film thickness of 100 μm. The properties of this porous film were as follows.

[0040] Deflection temperature under load: 130℃ Thickness: 100μm Percentage of holes in the entire film: 42% Porous film (C-2) A porous film was produced in the same manner, except that the resin used was changed from PPS resin to PP resin (Prime Polypro J105G manufactured by Prime Polymer Co., Ltd.) The properties of this porous film (C-2) are as follows.

[0041] Deflection temperature under load: 100℃ Thickness: 100μm Percentage of holes in the entire film: 48% ·Porous film (C-3) A porous film was produced in the same manner, except that the resin used was changed from PPS resin to PA resin ("Amilan" CM1017, manufactured by Toray Industries, Inc. The properties of this porous film (C-3) are as follows.

[0042] Deflection temperature under load: 190℃ Thickness: 100μm Percentage of holes in the entire film: 45% <Thermoplastic film without porous structure> Resin film (F-1) PPS resin (Toray Industries, Inc., "TORELINA" M2888) pellets were hot pressed to prepare a film-like substrate having a thickness of 100 μm, to obtain a resin film (F-1). The properties of this resin film were as follows:

[0043] Deflection temperature under load: 130℃ Thickness: 100μm Percentage of holes in the entire film: 0% · Resin film (F-2) PP resin (Prime Polypro J105G manufactured by Prime Polymer Co., Ltd.) pellets were hot pressed to prepare a film-like substrate having a thickness of 100 μm, to obtain a resin film (F-2). The properties of this resin film were as follows:

[0044] Deflection temperature under load: 100℃ Thickness: 100μm Percentage of holes in the entire film: 0% Resin film (F-3) PA resin ("Amilan" CM1007, manufactured by Toray Industries, Inc.) pellets were hot pressed to prepare a film-like substrate having a thickness of 100 μm, to obtain a resin film (F-3). The properties of this resin film were as follows:

[0045] Deflection temperature under load: 182℃ Thickness: 100μm Percentage of holes in the entire film: 0% Example 1 From the thermosetting prepreg and the porous film (C-1) prepared by the above-mentioned method, 12 rectangular sheets having a predetermined size were cut out, and 12 prepregs were laminated so that the fiber direction was [0° / 90° / 0° / 90° / 0° / 90° / 90° / 0° / 90° / 0° / 90° / 0°], with the direction of the long side of the rectangular cut sheet being 0°. Furthermore, one porous film (C-1) was laminated on the surface to obtain a preform.

[0046] Next, the preform was heated in an autoclave at 90°C for 1 hour while applying a surface pressure of 0.6 MPa, and then heated at 135°C for 2 hours to harden the thermosetting resin, thereby obtaining a laminate with an average thickness of 1.5 mm. The properties of the obtained laminate are shown in Table 1. After cutting the obtained laminate with a diamond cutter, the thermoplastic film was peeled off from the end after cutting, and it was firmly adhered, and the thermoplastic film was broken.

[0047] Example 2 A laminate was produced in the same manner as in Example 1, except that the porous film (C-2) was used instead of the porous film (C-1). After cutting the obtained laminate with a diamond cutter, the thermoplastic film was peeled off from the cut end, and was found to be firmly attached, and the thermoplastic film was broken.

[0048] Example 3 A laminate was produced in the same manner as in Example 1, except that the porous film (C-3) was used instead of the porous film (C-1). After cutting the obtained laminate with a diamond cutter, the thermoplastic film was peeled off from the cut end, and was found to be firmly attached, and the thermoplastic film was broken.

[0049] Comparative Example 1 A laminate having an average thickness of 1.6 mm was obtained in the same manner as in Example 1, except that a resin film (F-1) without a porous structure was used instead of the porous film (C-1). When the obtained laminate was cut with a diamond cutter, the thermoplastic film was easily peeled off from the cut end.

[0050] Comparative Example 2 A laminate having an average thickness of 1.6 mm was obtained in the same manner as in Example 1, except that a resin film (F-2) having no porous structure was used instead of the porous film (C-1). When the obtained laminate was cut with a diamond cutter, the thermoplastic film peeled off.

[0051] Comparative Example 3 A laminate was produced in the same manner, except that a resin film (F-3) without a porous structure was used instead of the porous film (C-1). After cutting the obtained laminate with a diamond cutter, the thermoplastic film was peeled off from the burr at the end, and it was possible to peel off the thermoplastic film from the end after cutting, although it was adhered.

[0052] [Table 1]

Claims

1. A laminate in which a thermoplastic film (C) having a porous structure is laminated on the surface of a layer consisting of reinforcing fibers (A) and a thermosetting resin (B), wherein the diameter of the pores of the thermoplastic film (C) is 0.01 μm or more and 30 μm or less.

2. 2. The laminate according to claim 1, wherein a portion of the thermosetting resin (B) is contained within pores of the thermoplastic film (C).

3. 3. The laminate according to claim 1, wherein the thermoplastic film (C) has a thickness of 1 μm or more and 500 μm or less.

4. The laminate according to claim 1 or 2, wherein the thermoplastic film (C) contains a resin having a deflection temperature under load of 100° C. or higher.

5. 3. The laminate according to claim 1 or 2, wherein the porous structure of the thermoplastic film (C) contains fibrillated portions.

6. The laminate according to claim 1 or 2, wherein the thermosetting resin (B) is an uncured thermosetting resin.

7. 3. The laminate according to claim 1, wherein the thermosetting resin (B) is a cured thermosetting resin.

8. A method for producing a laminate, comprising the steps of laminating a thermoplastic film (C) having a porous structure on at least one surface of a prepreg containing an uncured thermosetting resin (B) and reinforcing fibers (A), and then impregnating the thermosetting resin (B) into pores of the thermoplastic film (C) having a porous structure by heating and pressurizing.

9. The method for producing a laminate according to claim 8, further comprising a step of curing the uncured thermosetting resin (B).

10. 9. The method for producing a laminate according to claim 8, further comprising the step of impregnating the pores of the thermoplastic film (C) having a porous structure with the thermosetting resin (B) by heating and pressurizing, and simultaneously curing the uncured thermosetting resin (B).

11. The method for producing a laminate according to claim 9 or 10, wherein the step of curing the uncured thermosetting resin (B) includes a step of heating at a temperature lower than the deflection temperature under load of the thermoplastic film (C).

Citation Information

Patent Citations

  • Surface-modified member, coated object, production method for surface-modified member, and production method for coated object

    WO2022181423A1